2013
DOI: 10.1371/journal.pone.0076503
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autophagy Is an Early Response to Gefitinib and a Potential Therapeutic Target in Breast Cancer

Abstract: Gefitinib (Iressa®, ZD1839) is a small molecule inhibitor of the epidermal growth factor receptor (EGFR) tyrosine kinase. We report on an early cellular response to gefitinib that involves induction of functional autophagic flux in phenotypically diverse breast cancer cells that were sensitive (BT474 and SKBR3) or insensitive (MCF7-GFPLC3 and JIMT-1) to gefitinib. Our data show that elevation of autophagy in gefitinib-treated breast cancer cells correlated with downregulation of AKT and ERK1/2 signaling early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 59 publications
4
63
0
Order By: Relevance
“…EGFR targeted therapy has been characterised as a potent autophagy-inducing stimulus in cancer cells 17,19,42,44,45,[48][49][50] Interestingly, we found that all CRC cell lines utilised in this work exhibit basal autophagic flux irrespective of their PI3K or KRAS mutational status. Although earlier studies have suggested that autophagy can be regulated in an mTORC1-independent manner, [13][14][15][16][17][18][19] the role of basal autophagy in cancer remains elusive.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…EGFR targeted therapy has been characterised as a potent autophagy-inducing stimulus in cancer cells 17,19,42,44,45,[48][49][50] Interestingly, we found that all CRC cell lines utilised in this work exhibit basal autophagic flux irrespective of their PI3K or KRAS mutational status. Although earlier studies have suggested that autophagy can be regulated in an mTORC1-independent manner, [13][14][15][16][17][18][19] the role of basal autophagy in cancer remains elusive.…”
Section: Discussionmentioning
confidence: 86%
“…It has been proposed by us and others that in established tumours autophagy plays a pro-survival role, 28,39,41,42,45,46,57 in particular upon starvation or downstream inhibition of oncogenic kinase signalling, both of which result in inhibition of the main autophagy inhibitor, the PI3K/AKT/mTORC1 pathway. However, little is known on the role of autophagy and autophagy-like pathways in the presence of active PI3K/AKT/mTORC1 signalling in cancer cells, due to mutations in either PI3K or RAS pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…we examined whether cell viability and HER2 protein expression were affected when lysosomal function was compromised using bafilomycin A1, a macrolide antibiotic that passively permeates into lysosomes and increases lysosomal pH, which disrupts lysosomal activity. 50, 51 Figure 6C indicates that pretreatment with bafilomycin A1 followed by co-incubation with HApt-MNPs increased cell viability (by ~25%) and upregulated HER2 (by ~38%) compared to cells treated with the same concentration of HApt-MNPs without bafilomycin A1 to block lysosomal function ( Figure 6D). The increase in pH inside cells treated with bafilomycin A1 was confirmed by LysoTracker Red staining ( Figure S7).…”
Section: Hapt-mnps Accumulate In Lysosomes and Induce Degradation Of mentioning
confidence: 94%